Ich will auch in die Schule gehen - Lindgren, Astrid,Wikland, Ilon,Hacht, Silke von (Oetinger, 1991)
Five-year-old Lena longs to go to school and is excited when her older brother takes her with him to spend the day at his school.
Aus dem Schwed. übers
Keywords: Deutsch; Brothers and sisters; German language; Schools; Schulkind; Bilderbuch; Vorschulkind